2007
DOI: 10.1074/jbc.m611840200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Pseudomonas aeruginosa Lol System as a Lipoprotein Sorting Mechanism

Abstract: Escherichia coli lipoproteins are localized to either the inner or the outer membrane depending on the residue that is present next to the N-terminal acylated Cys. Asp at position 2 causes the retention of lipoproteins in the inner membrane. In contrast, the accompanying study (9) revealed that the residues at positions 3 and 4 determine the membrane specificity of lipoproteins in Pseudomonas aeruginosa. Since the five Lol proteins involved in the sorting of E. coli lipoproteins are conserved in P. aeruginosa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…aeruginosa encodes homologs to each of the lolABCDE genes, and the LolCDE complex from P. aeruginosa recently was shown to release lipoproteins to the LolA chaperone (21). Reconstituted proteoliposomes with the LolCDE from P. aeruginosa did not release to LolA lipoproteins that contained the Lys ϩ3 Ser ϩ4 inner membrane retention signal.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa encodes homologs to each of the lolABCDE genes, and the LolCDE complex from P. aeruginosa recently was shown to release lipoproteins to the LolA chaperone (21). Reconstituted proteoliposomes with the LolCDE from P. aeruginosa did not release to LolA lipoproteins that contained the Lys ϩ3 Ser ϩ4 inner membrane retention signal.…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular mechanisms by which lipoproteins are targeted to the outer membrane have been extensively studied in E. coli, less is known about the Lol system in other gammaproteobacteria. For example, some work has been done to profile the proteins from P. aeruginosa, which showed that the five P. aeruginosa Lol proteins are responsible for the sorting of lipoproteins to the outer membrane, as in the case of E. coli lipoproteins (45). However, it was also shown that there are differences between E. coli and P. aeruginosa in the lipoprotein-sorting signals that dictate retention in the inner membrane or transfer to the outer membrane (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some work has been done to profile the proteins from P. aeruginosa, which showed that the five P. aeruginosa Lol proteins are responsible for the sorting of lipoproteins to the outer membrane, as in the case of E. coli lipoproteins (45). However, it was also shown that there are differences between E. coli and P. aeruginosa in the lipoprotein-sorting signals that dictate retention in the inner membrane or transfer to the outer membrane (45,46). It is possible that the differences between the E. coli and P. aeruginosa Lol systems are significant enough that the pyridineimidazoles are not active against the P. aeruginosa LolCDE complex.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear why Asp at position 2 can function as an inner membrane signal but is not used for many inner membrane lipoproteins in P. aeruginosa. 66) Finally, many lipoproteins still have no known function even in E. coli. Since lipoproteins are involved in various envelope activities, their structures and functions must be clarified in order to understand how bacterial envelopes are formed and maintained.…”
Section: Problems To Be Solvedmentioning
confidence: 99%